A systematic review of real-world diabetes prevention programs: learnings from the last 15 years. (December 2015) - Aziz, Zahra; Absetz, Pilvikki; Oldroyd, John; Pronk, Nicolaas; Oldenburg, Brian
Abstract Background The evidence base for the prevention of type 2 diabetes mellitus (T2DM) has progressed rapidly from efficacy trials to real-world translational studies and practical implementation trials over the last 15 years. However, evidence for the effective implementation and translation of diabetes programs and their population impact needs to be established in ways that are different from measuring program effectiveness. We report the findings of a systematic review that focuses on identifying the critical success factors for implementing diabetes prevention programs in real-world settings. Methods A systematic review of programs aimed at diabetes prevention was undertaken in order to evaluate their outcomes using the penetration, implementation, participation, and effectiveness (PIPE) impact metric. A search for relevant articles was carried out using PubMed (March 2015) and Web of Science, MEDLINE, CENTRAL, and EMBASE. A quality coding system was developed and included studies were rated independently by three researchers. Results Thirty eight studies were included in the review. Almost all (92 %) provided details onparticipation ; however, only 18 % reported the coverage of their target population (penetration ).Program intensity or implementation —as measured by frequency of contacts during first year and intervention duration—was identified in all of the reported studies, and 84 % of the studies also reported implementation fidelity; however, only 18 % of studies employed quality assurance measures to assess the extent to which the program was delivered as planned. Sixteen and 26 % of studies reported 'highly' or 'moderately' positive changes (effectiveness ) respectively, based on weight loss. Six (16 %) studies reported 'high' diabetes risk reduction but 'low' to 'moderate' weight loss only. Conclusion Our findings identify that program intensity plays a major role in weight loss outcomes. However, programs that have high uptake—both in terms of good coverage of invitees and their willingness to accept the invitation—can still have considerable impact in lowering diabetes risk in a population, even with a low intensity intervention that only leads to low or moderate weight loss. From a public health perspective, this is an important finding, especially for resource constrained settings. More use of the PIPE framework components will facilitate increased uptake of T2DM prevention programs around the world.